Filter EMI Aktif menggunakan Op-Amp untuk Mereduksi Near-Field EMI pada PCB - Wahyudi Nasrianza; Mohammad Yanuar Hariyawan (ABEC Indonesia, 2021)
Electronic devices often cause an increase in Electromagnetic Interference (EMI) which has two types, namely Conducted Emission and Radiated Emission. One solution to reduce EMI mitigation is to use an EMI filter. Operational Amplifiers (Op Amps) are a form of Linear IC which has a function to amplify electrical signals. This final project will discuss the use of op-amps to minimize near-field EMI. In this case, an op-amp circuit is added to reduce the EMI of the clock source. One of the most important characteristics of the op amp is its extremely low output impedance. This study will design an active EMI filter to reduce conducted emission noise using an active EMI filter (AEF). The designed AEF filter provides excellent conducted emission noise attenuation with pre-filtered noise conducted at 118 dB which is reduced to 108.95 dB and provides excellent conducted emission noise attenuation (up to 9.05 dB).